Periradicular Tissue Responses to Biologically Active Molecules or MTA When Applied in Furcal Perforation of Dogs' Teeth - Anna Zairi; Theodoros Lambrianidis; Ourania Pantelidou; Serafim Papadimitriou; Dimitrios Tziafas (International Journal of Dentistry)
The aim of this study was the comparative evaluation of inflammatory reactions and tissue responses to four growth factors, or mineral trioxide aggregate (MTA), or a zinc-oxide-eugenol-based cement (IRM) as controls, when used for the repair of furcal perforations in dogs’ teeth. Results showed significantly higher inflammatory cell response in the transforming growth factorβ1 (TGFβ1) and zinc-oxide-eugenol-based cement (IRM) groups and higher rates of epithelial proliferation in the TGFβ1, basic fibroblast growth factor (bFGF), and insulin growth factor-I (IGF-I) groups compared to the MTA. Significantly higher rates of bone formation were found in the control groups compared to the osteogenic protein-1 (OP-1). Significantly higher rates of cementum formation were observed in the IGF-I and bFGF groups compared to the IRM. None of the biologically active molecules can be suggested for repairing furcal perforations, despite the fact that growth factors exerted a clear stimulatory effect on cementum formation and inhibited collagen capsule formation. MTA exhibited better results than the growth factors.